2011
DOI: 10.1007/s00894-011-1018-3
|View full text |Cite
|
Sign up to set email alerts
|

Homology modeling, molecular dynamics, e-pharmacophore mapping and docking study of Chikungunya virus nsP2 protease

Abstract: To date, no suitable vaccine or specific antiviral drug is available to treat Chikungunya viral (CHIKV) fever. Hence, it is essential to identify drug candidates that could potentially impede CHIKV infection. Here, we present the development of a homology model of nsP2 protein based on the crystal structure of the nsP2 protein of Venezuelan equine encephalitis virus (VEEV). The protein modeled was optimized using molecular dynamics simulation; the junction peptides of a nonstructural protein complex were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 32 publications
1
60
0
Order By: Relevance
“…For instance, Bassetto et al reported that Cys1013 and His1083 (the numbering is according to the CHIKV nsP2 sequence) in the homology model of the nsP2 protease were the catalytic residues compared to Cys477 and His546 in the VEEV nsP2 protease through a sequence alignment between the CHIKV nsP2 protease and the VEEV nsP2 protease. In contrast, similarly based the sequence alignment, Singh et al predicted that the active site residues interacting with the peptide substrate include Lys1045, Gly1176, His1222 and Lys1239 without explicitly identifying the catalytic residues [19]. In this work, structural alignment of the nsP2 proteases from three alphaviruses, CHIKV (PDB id: 3TRK), Venezuelan equine encephalitis virus (VEEV, PDB id:…”
Section: Identification Of the Active Site Of The Nsp2 Proteasementioning
confidence: 98%
See 4 more Smart Citations
“…For instance, Bassetto et al reported that Cys1013 and His1083 (the numbering is according to the CHIKV nsP2 sequence) in the homology model of the nsP2 protease were the catalytic residues compared to Cys477 and His546 in the VEEV nsP2 protease through a sequence alignment between the CHIKV nsP2 protease and the VEEV nsP2 protease. In contrast, similarly based the sequence alignment, Singh et al predicted that the active site residues interacting with the peptide substrate include Lys1045, Gly1176, His1222 and Lys1239 without explicitly identifying the catalytic residues [19]. In this work, structural alignment of the nsP2 proteases from three alphaviruses, CHIKV (PDB id: 3TRK), Venezuelan equine encephalitis virus (VEEV, PDB id:…”
Section: Identification Of the Active Site Of The Nsp2 Proteasementioning
confidence: 98%
“…The compounds from library NCI Diversity Set II were docked to the entire protein (the nsP2 protease) with a grid box placed at either the centre at the binding site 1 (VST1) or at the centre of the protein (VST2). The binding site 1 (Pocket 1), including the key residues for interactions (Lys1045, Gly1176, His1222 and Lys1239), was taken from the published data by Singh et al [19]. The binding modes of the compounds were ranked by their predicted binding affinities.…”
Section: Blind Dockings and Focused Dockings To Identify Potential Bimentioning
confidence: 99%
See 3 more Smart Citations